Karakteristik Habitat Ikan Cupang Alam Endemik Betta Burdigala Di Perairan Dusun Tuing, Kabupaten Bangka - Ramadani, Reza (Fishery Product Technology Study Program, Yudharta University, Pasuruan, 2025)
The natural betta fish Betta Burdigala is one of the endemic fish found on Bangka Island. The current status of the natural betta fish Betta burdigala on Bangka Island is endangered, IUCN CR (Critically Endangered). The aim of this research is to provide an overview of the characteristics of the Betta Burdigala habitat, so that it can become basic information in maintaining the existence of the Betta Burdigala, thereby avoiding extinction. Fish whose existence is threatened with extinction due to habitat destruction due to tin mining activities and the conversion of forests to oil palm plantations, as well as excessive exploitation, as well as the large spread of foreign fish entering the waters of Bangka Island. Research conducted in the waters of Bangka Regency and South Bangka Regency in March – April 2024 discussed the habitat characteristics of the endemic natural betta fish Betta Burdigala. According to the study's findings, the Betta burdigala fish prefers brownish peat swamp waters with a pH range of 3 to 5.